Relationship of blood glucose concentration at arrival to performance and carcass characteristics of beef heifers - Loe, E.R.; Kessen, T.J.; Montgomery, Sean P.; Sindt, J.J.; Sulpizio, M.J.; Pike, J.N.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Crossbred yearling heifers (n = 394) were used to compare the effect of high or low blood glucose measured at arrival on feedlot performance and carcass characteristics. A blood sample was collected when heifers arrived at the Beef Cattle Research Center, and heifers were sorted into two groups: high or low blood glucose. The mean blood glucose concentration of the heifers was 57 ± 2 mg/dL in the low group and 78 ± 2 mg/dL in the high group. Heifers that had low blood glucose at arrival consumed more feed (P=0.02), tended to have increased final bodyweight and rate of gain (P<0.10), had increased backfat thickness (P<0.05), and tended to have heavier hot carcass weights and fewer standard carcasses (P<0.10) compared with heifers that had high blood glucose at arrival.
Keywords: Beef; Blood glucose; Performance; Carcass characteristics; Heifers